Remodeling tumor microenvironment with natural products to overcome drug resistance - Zhang, Wanlu; Li, Shubo; Li, Chunting; Li, Tianye; Huang, Yongye (Frontiers in Immunology, 2022)
With cancer incidence rates continuing to increase and occurrence of resistance in drug treatment, there is a pressing demand to find safer and more effective anticancer strategy for cancer patients. Natural products, have the advantage of low toxicity and multiple action targets, are always used in the treatment of cancer prevention in early stages and cancer supplement in late stages. Tumor microenvironment is necessary for cancer cells to survive and progression, and immune activation is a vital means for the tumor microenvironment to eliminate cancer cells. A number of studies have found that various natural products could target and regulate immune cells such as T cells, macrophages, mast cells as well as inflammatory cytokines in the tumor microenvironment. Natural products tuning the tumor microenvironment via various mechanisms to activate the immune response have immeasurable potential for cancer immunotherapy. In this review, it highlights the research findings related to natural products regulating immune responses against cancer, especially reveals the possibility of utilizing natural products to remodel the tumor microenvironment to overcome drug resistance.